Diagnosis of competences and interactive, communication and language skills of a patient with progressive nonfluent aphasia - Gliwa, Renata (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
This article assesses the competences and interactive, communication and language skills (with particular emphasis on lexical-semantic skills) of patients diagnosed with primary non-fluent aphasia and deep dementia. The comparison was made to indicate disproportions in the field of preserved abilities and deficits in the area of abovementioned abilities and to show the necessity of using detailed speech therapy in the discussed type and degree of dementia. It is necessary to be able to support islet-preserved selected cognitive functions for as long as possible, and thus to have the possibility of contact with the sick for as long as possible, improving the comfort of his and his caregivers’ lives. The article uses research material about a 76-year-old woman.